Substance P blockade effects on bone marrow hematopoiesis in secondary chronic inflammation - Shevchenko, O. M.; Sych, V. O. (Journal of Education, Health and Sport, 2020)
Inflammation is defined by the features of bone marrow hematopoiesis. Thus, an objective of the study was to determine the substance P inhibition effects on bone marrow hematopoiesis in secondary chronic carrageenan-induced inflammation in experimental prospective controlled study on 132 white male WAG rats. On the background of blockade of substance P, the course of inflammation was characterized by a less intense neutrophilic reaction and the development of the lymphocyte component at earlier stages of inflammation. Given the peculiarities of bone marrow hematopoiesis in carrageenan secondary chronic inflammation on the background of its suppression, the influence of substance P on the course of chronic inflammation is certain.